2018
DOI: 10.1038/s41598-018-20428-8
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation induces sparse distributions of locally modulated neuronal activity

Abstract: Deep brain stimulation (DBS) therapy is a potent tool for treating a range of brain disorders. High frequency stimulation (HFS) patterns used in DBS therapy are known to modulate neuronal spike rates and patterns in the stimulated nucleus; however, the spatial distribution of these modulated responses are not well understood. Computational models suggest that HFS modulates a volume of tissue spatially concentrated around the active electrode. Here, we tested this theory by investigating modulation of spike rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Even though excitatory inputs are mainly distributed further from the soma, they are more dense than inhibitory inputs [25] and played a stronger role in determining antidromic activation than inhibitory inputs. Earlier recordings made in thalamic neurons exhibited both excitation and inhibition within the stimulated nucleus [52], which may stem in part from the prevalence or strength of excitatory relative to inhibitory inputs within the thalamus [53]. Similar responses were recorded in STN neurons during STN DBS [18] and globus pallidus externus (GPe) neurons during GPe DBS [9].…”
Section: Discussionmentioning
confidence: 91%
“…Even though excitatory inputs are mainly distributed further from the soma, they are more dense than inhibitory inputs [25] and played a stronger role in determining antidromic activation than inhibitory inputs. Earlier recordings made in thalamic neurons exhibited both excitation and inhibition within the stimulated nucleus [52], which may stem in part from the prevalence or strength of excitatory relative to inhibitory inputs within the thalamus [53]. Similar responses were recorded in STN neurons during STN DBS [18] and globus pallidus externus (GPe) neurons during GPe DBS [9].…”
Section: Discussionmentioning
confidence: 91%
“…While one could interpret the data based on a volume of tissue activated (VTA) approach, there is a growing number of studies showing that the VTAs are significantly less accurate than the pathway-specific approach adopted in this study ( Gunalan et al, 2017 ; Howell et al, 2019 ). Additionally, the use of volumes is a misnomer when considering neuronal responses to stimulation, which have shown that electrical stimulation results in a sparse density map of neuronal activation ( Histed et al, 2009 ; Xiao et al, 2018 ; Michelson et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that DBS in the subthalamic nucleus (Welter et al, 2004) and internal globus pallidus (Dostrovsky et al, 2000) of humans showed decreased neuronal firing rates at the site of DBS during stimulation. In a more recent study, DBS at the motor thalamus has been shown to inhibit spike activity and modulate spike patterns locally using a single-unit electrophysiology measurement (Xiao et al, 2018). In this study, we also used a sophisticated single-unit electrophysiology and characterized the neural activity pattern at the M1 to determine DBS function distally.…”
Section: Discussionmentioning
confidence: 99%